The effect of long-term drug use on rational use of medicines in children with medical illness - Yaşar Topal; Emine Neşe Yeniçeri; Aynur Özdemir (SERNEV, 2023)
Introduction: This study was conducted to investigate the effect of long-term drug use due to medical diseases on rational drug use in children, using data obtained from parents. It is a cross-sectional study.Methods: Among the 288 parents who applied to the pediatric outpatient clinics of Muğla Training and Research Hospital between January 1, 2022 and March 31, 2022; 144 people with children aged 0-12 who have a chronic disease and have been using regular medication for at least three months are included in the research group, 144 people who did not have a chronic disease and did not use medication constantly were determined as the control group. In addition to the form containing sociodemographic data and questions to evaluate rational drug use awareness, knowledge, attitudes and behaviors, the "Parental Attitude Scale For Rational Drug Use (PASRDU)" was answered through a face-to-face interview. Data analysis was conducted with SPSS 26 program with a confidence level of 95%. Parental Attitude Scale For Rational Drug Use scores showed normal distribution in both groups. Independent samples t-test was used to compare Parental Attitude Scale For Rational Drug Use scores according to groups, a chi-square test was used to compare the relationship between groups and categorical (grouped) variables, and a two-way ANOVA test was used to compare demographic characteristics and group variables according to Parental Attitude Scale For Rational Drug Use scores.Results: Of the parents participating in the study, 67.71% were mothers and 32.29% were fathers. The average age was 34.88±6.44 years in the research group and 33.57±6.57 years in the control group. The rates of having chronically ill individuals at home and individuals constantly using medication at home are higher in the research group and are statistically significant. While the presence of leftover or spare medication at home was be similar in the research and control groups, the rate of using these medications when necessary was 45.8% in the research group and 56.3% in the control group. While 43.1% of those in the research group did not give over-the-counter medicine to their children, this rate was 16% in the control group. The control group uses over-the-counter vitamins twice as much as the research group. The most commonly used over-the-counter medication in the entire population is antipyretics with a rate of 44.79%. The scores of the research group in Parental Attitude Scale For Rational Drug Use and its subscales are higher than the control group and are statistically significant. The place of residence for the longest time, educational level, having too much medication at home, and using non-prescription medication statistically affect the scores. In addition, the duration of the disease of the children in the research group significantly affected the Parental Attitude Scale For Rational Drug Use total score and the Accurate and Conscious Use subscale, and the disease group significantly affected the Effective and Safe Use subscale score.Conclusion: According to our research, long-term use of medication in children due to medical illness affects rational drug use. Accurate and current information is required in the preparation and use of drugs used in children due to the change in dosage and pharmaceutical form depending on age. In addition, herbal products and food supplements are also used during childhood. Therefore, the knowledge, attitudes and behaviors of healthcare professionals and parents affect children's health. As studies on rational drug use in different regions in our country increase, more detailed and separate planning can be made for drugs used in childhood while preparing education and policies for rational drug use.